Bioaccumulation in the gut and liver causes gut barrier dysfunction and hepatic metabolism disorder in mice after exposure to low doses of OBS. (August 2019) - Wang, Caiyun; Zhang, Yi; Deng, Mi; Wang, Xia; Tu, Wenqing; Fu, Zhengwei; Jin, Yuanxiang
Abstract: The compound sodium ρ-perfluorous nonenoxybenzene sulfonate (OBS), a new kind of perfluoroalkyl and polyfluoroalkyl compound, is a surfactant for increasing oil production, and it has been widely detected in various organisms. Because of its wide use, OBS is detectable in the environment. However, knowledge about the biological toxicity of OBS to animals is very limited. Here, male mice were exposed to 0, 0.1, 1 or 10 μg/L of OBS for 6 weeks via drinking water. It was demonstrated that OBS was highly bioaccumulated both in the liver and gut in the mice after low doses of OBS exposure. Curiously, a low dose of OBS exposure also caused gut barrier dysfunction by decreasing mucus secretion and altering Ionic transport in the gut via the CFTR pathway. In addition, liver function was influenced by OBS at both the histopathological and physiological levels. Hepatic transcriptomics and metabolomics analysis showed a total of 1157 genes, and multiple metabolites changed significantly in the livers of mice exposed to low-dose OBS for 6 weeks. The functions of these changed genes and metabolites are tightly related to glycolysis, fatty acid synthesis, fatty acid transport, and β-oxidation. All these results indicate that the liver and gut are important target tissues for OBS exposure. Importantly, it is possible that high levels of bioaccumulation of OBS in the gut and liver might directly cause gut barrier dysfunction and hepatic metabolism disorder in mice. Highlights: OBS could accumulated in the liver and gut of mice after six weeks exposure OBS significantly inhibits the secretion of gut mucus in mice OBS could cause increase of ionic transport in the gut via CFTR dysfunction in mice OBS exposure cause hepatic metabolism disorder in mice